Bridging the Digital Divide: Indonesian EFL Higher Education Students' Perceptions of Web-Based Collaborative Writing Tools - Ardiningtyas, Sri Yulianti; Jabu, Baso; Iskandar, Iskandar (Universitas Cokroaminoto Palopo, 2025)
This research explores the perceptions of Indonesian English as a Foreign Language (EFL) higher education students towards the use of web-based collaborative writing tools, focusing on Padlet, in argumentative essay writing. Employing a qualitative case study design, the study utilized semi-structured interviews with ten students from an English Education Program in Makassar, Indonesia. The data, analyzed through thematic analysis, revealed that students perceive Padlet as highly useful due to its ability to organize ideas, facilitate collaboration and feedback, enhance accessibility and flexibility, improve writing skills, and offer time efficiency. Additionally, students found Padlet easy to use, citing its intuitive interface, ease of getting started, seamless integration into their workflow, adaptability to various writing stages, provision of control over the writing process, and minimal technical issues. These findings underscore the potential of Padlet in enhancing EFL writing instruction by providing an interactive and visually appealing platform that addresses the specific needs of EFL learners in argumentative essay writing. The study concludes that web-based collaborative tools like Padlet can significantly contribute to developing confident and competent writers in EFL contexts, highlighting the importance of integrating such technologies to bridge the digital divide and transform traditional writing pedagogies.